An analysis and commentary on Riddah in Malaysia - Ong, Guan Boon; Zuhair Rosli (Penerbit Universiti Kebangsaan Malaysia, 2021)
Riddah originally from the Arabic language Al-Riddah means apostasy while in Malaysia it is commonly referred to as murtad. Riddah is part of the hudud offences whereby the punishments are clearly spelt out by Al-Quran and Hadith which cannot be added and deducted, or altered because it has been determined by Allah. For riddah, most of the Islamists jurists hold on to ahad hadith (a single hadith) which is still disputed as a basis of law but most of them agreed that only when an apostate act against Islam then he or she must be killed. In the practical aspect, application of Islamic law in Malaysia is predominantly derived from statute and even for the riddah punishment the Syariah Court can only impose a punishment not more than 3 years of imprisonment, fine not more than RM5,000 and whipping not more than 6 strokes which is in stark contrast with the punishment agreed upon by Islamists jurists. Apart from this sentencing power, other issues surrounding riddah will be discussed in depth in this article with the aim to find the best practise which is acceptable for the whole of Malaysia.